Kinematics analysis on the Chinese elite athletes Tan Sixin's balance beam movement of change leg ring leap - Xiong, L.; Zhou, J.; Su, Q. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to obtain a series of kinematics parameters of Tan Sixin's change leg ring leap with the help of software and to make kinematics analysis, in order to reveal the kinematic rules and technical characteristics of the change leg ring leap movement, thus providing theoretical basis and reference for athletes to consummate technique and coaches to guide training.